2020
DOI: 10.1002/admt.202000326
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Balancing Redox Mediators for High Color Contrast Electrochromism on Polyoxometalates

Abstract: POMs) recently emerged as promising inorganic materials due to their varying structures, high electrochemical activities, and EC performances. [11,12] The most common and widely investigated POM structure is the Keggin structure, which is applied in biochemical, electrochemical, and catalytic areas. [13] However, studies on the EC properties of Keggin-structured POMs are limited, and their reported EC performances were inferior to other POM types. [14] Several attempts were made to improve the EC performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…[14][15][16] It is worth noting that POM-based electrochromic materials suffer from limited electrolyte choices. 17 Acid aqueous electrolyte media facilitate the reversible and rapid multi-electron transfer process within POMs, and therefore they usually exhibit high electrochemical activity. 18 Unfortunately, acid-aqueous electrolyte media are not appropriate for device fabrication, since the H + tends to corrode the electrode surface, and extra H + in water media could be polarized easily to generate hydrogen bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It is worth noting that POM-based electrochromic materials suffer from limited electrolyte choices. 17 Acid aqueous electrolyte media facilitate the reversible and rapid multi-electron transfer process within POMs, and therefore they usually exhibit high electrochemical activity. 18 Unfortunately, acid-aqueous electrolyte media are not appropriate for device fabrication, since the H + tends to corrode the electrode surface, and extra H + in water media could be polarized easily to generate hydrogen bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…This work provided an alternative method for improving the performance of POMs-based capacitor electrode materials. In addition, Wang et al [14] reported a high-performance PW 12 -based EC device, wherein the optical contrast of the optimised device containing an I − /I 3− redox couple in the electrolyte reached 59.4%. The PW 12 -EC device also showed a fast response time for bleaching and colouration.…”
Section: Introductionmentioning
confidence: 99%
“…19 These properties make them an ideal material for EC and pseudocapacitor materials. For example, Wang et al 20 reported POMs-based electrochromic devices (ECDs) with high optical contrast (59.4%) and fast response time (t c = 3.1 s, t b = 1.9 s), in which Keggin type polyanion PW 12 O 40 3À coated porous TiO 2 nanoparticle films were used as the working electrode. A non-aqueous charge-balancing electrolyte with a redox couple I À /I 3À can improve the EC performance of ECDs.…”
Section: Introductionmentioning
confidence: 99%